PENGARUH PEMBAGIAN TUGAS DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA PEMERINTAHAN KECAMATAN SIBOLGA KOTA - Lenny Situmorang; Mansur Tanjung; Yacub Hutabarat (CV. ALIM'SPUBLISHING, 2023)
The division of tasks is a series of activities carried out in order to determine what should be done or what the work is and who should do it. Competence is an ability to carry out or do a job that is based on skills and is supported by the work attitude demanded by the job. Competence denotes skills and knowledge characterized by professionalism. in this study, namely the formulation of whether the division of tasks and competencies jointly affect the performance of employees in the Sibolga Kota District Government? This study aims to determine how much influence the division of tasks and competencies has on employee performance in the Sibolga Kota District Government. The provisional hypothesis is that the division of tasks and competencies has a joint effect on the performance of employees in the Sibolga Kota District Government. The population is 85 people and used as a sample. Data collection techniques using library research and field research. The results of the research show that the division of labor and competency variables can influence the performance variables of employees in the Sibolga Kota District Government by 54.2%. The division of tasks and competencies jointly or simultaneously has a positive and significant effect on the performance of employees in the Sibolga Kota District Government. Where the Fcount value is greater than the Ftable value (38.510 > 3.11). Partially the division of labor and competence has a positive and significant effect on employee performance in the Sibolga Kota District Government. Where the value of tcount = (2.373) is greater than the value of ttable (1.992), Partially the most dominant division of labor affects employee performance, meaning that the variable of division of labor is more decisive in improving employee performance compared to work involvement. Where the value of tcount = (4.453) is greater than the value of ttable (1.995).